Urgensi Evaluasi Pendidikan Anak Usia Dini Sebagai Upaya Peningkatan Indeks Pembangunan Manusia Di Provinsi Gorontalo - Suripto Suripto (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2010)
Early Childhood Education is an important step in creating a high quality human. Data on 2008 show that, 41% children had early childhood education. This paper presents the evaluation of early childhood education based on district and municipality in Gorontalo Province. The analysis tools are DEA-BCC-O model Solver. The results show that four districts and municipality include in efficient category which are Gorontalo Municipality, Gorontalo District, Gorontalo North District and Pohuwato District. Meanwhile, two districts are include in not efficient category which are Bone Bolango District and Boalemo District